SP2.1.14Remote examination of surgical skills is feasible and desirable during COVID crisis and beyond. (28th October 2021) - Marsh, Stephen; Bruce, Caroline; Blackmore, Alexander; Ichim, Petre; Sharma, Ajay; Paraoan, Marius
Abstract: Aims: We aimed to investigate the feasibility of employing Zoom technology to undertake structured remote examination of surgical skill during the COVID-19 crisis and beyond as a mean to complement remote training and supervision of basic laparoscopic skills. Methods: We have adapted a previously reported method of remote training and supervision of laparoscopic skills training successfully used with 7 trainees. Five consultant surgeons with established expertise in surgical education participated in remote mock examination of LapPass skills using Zoom technology. We assessed the feasibility of remote examination by assessing image quality on Maryland visual comfort scale and undertook a trainers' survey using a 5 point Lembert scale. Result: The remote examiners recorded excellent quality of views, identical in clarity and detail to the source images. Conclusions: We demonstrated the feasibility and the benefit of using modern internet technology in delivering a flexible approach to examination of surgical skills met with strong satisfaction by established trainers and trainees alike. All trainers supported the idea of introduction of remote examination as beneficial for all stakeholders and ready to replace face-to-face examination in specific settings. The surgical community should embrace, on a larger scale, the concept of remote supervision and examination whenever possible.